1997
DOI: 10.1076/phbi.35.1.55.13272
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition of Asexual Erythrocytic Forms of Plasmodium falciparum and P. berghei in vitro by Naphthylisoquinoline Alkaloid-Containing Extracts of Ancistrocladus and Triphyophyllum Species

Abstract: Naphthylisoquinoline alkaloid-containing extracts [1-20] of four species of the genus Ancistrocladus (A. barteri, A. heyneanus, A. robertsoniorum, and A. tectorius) and of Triphyophyllum peltatum have been examined for their antiplasmodial activity against asexual erythrocytic forms of Plasmodium falciparum (NF 54, clone A1A9) and P. berghei (Anka) in vitro. Incorporation of 3 H-hypoxanthine was measured in the presence of the test substances. The above mentioned plant species are used in several countries of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…AT extract has been traditionally used to treat malaria and dysentery and to improve blood circulation [12][13][14]. In addition to these functions, some studies have reported biological activities such as antiplasmodial [17,18], antiparasitic [13], antiviral [15], and antibacterial [18] activities for AT. In this study, the anti-obesity effect of 70% EtOH extract from the aerial parts of AT, mainly the leaves and stems, and its molecular mechanisms were investigated in 3T3-L1 adipocytes and HFD-fed C57BL/6J mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AT extract has been traditionally used to treat malaria and dysentery and to improve blood circulation [12][13][14]. In addition to these functions, some studies have reported biological activities such as antiplasmodial [17,18], antiparasitic [13], antiviral [15], and antibacterial [18] activities for AT. In this study, the anti-obesity effect of 70% EtOH extract from the aerial parts of AT, mainly the leaves and stems, and its molecular mechanisms were investigated in 3T3-L1 adipocytes and HFD-fed C57BL/6J mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AT root extract has been shown to have antiviral and antitumor activity [15,16] and to improve blood circulation [13]. Naphthylisoquinoline alkaloids with antiplasmodial activity have been isolated from AT stems and twigs [17,18]. In addition, other biological effects of AT leaf, bark, and root extracts have been investigated, including antibacterial [19], antifungal [19], antiparasitic [13], and antispasmodic [12] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Such extracts, naphthylisoquinoline alkaloids derived thereof, and synthetic related alkaloids are biologically very active (Bringmann and Pokorny 1995). Most remarkable are their in vitro activities against asexual erythrocytic stages of P. falciparum and P. berghei (Boyd et al 1995;Bringmann et al 1996a, b, c;FrancË ois et al 1994aFrancË ois et al , b, 1995FrancË ois et al , 1996FrancË ois et al , 1997c and against exo-erythrocytic stages of P. berghei in human hepatoma cells (FrancË ois et al 1997a, d). Recently, their curative in vivo potential against P. berghei has been demonstrated as well (FrancË ois et al 1997b).…”
Section: Introductionmentioning
confidence: 99%